PENGETAHUAN, SIKAP, DAN PERILAKU MASYARAKAT PESISIR PANTAI TENTANG AIR KELAPA SEBAGAI CAIRAN REHIDRASI DI DESA TONU JAYA TAHUN 2018 - Rahmawati Nyaisiah Borut; Ony Wibriono Angkejaya; Parningotan Yosi Silalahi (PAMERI, 2021)
Coconut water is one of natural resources that can be used as rehydration fluid because the electrolytes contained within are as same as in human body. Coconut water is rich in minerals such as potassium, calcium, magnesium and manganese, and low sodium levels. This was a cross-sectional descriptive study whose aim is to find out the knowledge, attitude, and behavior of coastal community about coconut water as rehydration fluid. The data was collected by spreading questionnaires among 101 respondents selected by using simple random sampling and the results are described using frequency distribution tables and graphics. The results showed that the knowledge of the community about coconut water as rehydration fluid can generally be categorised as sufficient (60,4%). The community’s attitude towards coconut water as rehydration fluid can be generally categorised as good (64,36%). The community’s behavior towards coconut water as rehydration fluid can be generally categorised as sufficient (74,26%).